Effects of halogens on European air-quality. (5th June 2017) - Sherwen, T.; Evans, M. J.; Sommariva, R.; Hollis, L. D. J.; Ball, S. M.; Monks, P. S.; Reed, C.; Carpenter, L. J.; Lee, J. D.; Forster, G.; Bandy, B.; Reeves, C. E.; et al.
Abstract : Halogens (Cl, Br) have a profound influence on stratospheric ozone (O3 ). They (Cl, Br and I) have recently also been shown to impact the troposphere, notably by reducing the mixing ratios of O3 and OH. Their potential for impacting regional air-quality is less well understood. We explore the impact of halogens on regional pollutants (focussing on O3 ) with the European grid of the GEOS-Chem model (0.25° × 0.3125°). It has recently been updated to include a representation of halogen chemistry. We focus on the summer of 2015 during the ICOZA campaign at the Weybourne Atmospheric Observatory on the North Sea coast of the UK. Comparisons between these observations together with those from the UK air-quality network show that the model has some skill in representing the mixing ratios/concentration of pollutants during this period. Although the model has some success in simulating the Weybourne ClNO2 observations, it significantly underestimates ClNO2 observations reported at inland locations. It also underestimates mixing ratios of IO, OIO, I2 and BrO, but this may reflect the coastal nature of these observations. Model simulations, with and without halogens, highlight the processes by which halogens can impact O3 . Throughout the domain O3 mixing ratios are reduced by halogens. In northern Europe this is due to a change in the background O3 advected into the region, whereas in southern Europe this is due to local chemistry driven by Mediterranean emissions. The proportion of hourly O3 above 50 nmol mol −1 in Europe is reduced from 46% to 18% by halogens. ClNO2 from N2 O5 uptake onto sea-salt leads to increases in O3 mixing ratio, but these are smaller than the decreases caused by the bromine and iodine. 12% of ethane and 16% of acetone within the boundary layer is oxidised by Cl. Aerosol response to halogens is complex with small (∼10%) reductions in PM2.5 in most locations. A lack of observational constraints coupled to large uncertainties in emissions and chemical processing of halogens make these conclusions tentative at best. However, the results here point to the potential for halogen chemistry to influence air quality policy in Europe and other parts of the world.